Prevalence of occupational contact dermatitis in cleaning service in the Sudirman campus of Udayana University - Jihan Prani Wibowo; Nyoman Suryawati; I Gusti Agung Ayu Elis Indira; I Gusti Agung Ayu Praharsini (Neurologico Spinale Medico Chirurgico, 2020)
Introduction: Occupational contact dermatitis is contact dermatitis caused by work-related exposures. While doing their work, cleaning service workers are facing various risks of occupational diseases, one of which is occupational contact dermatitis. The purpose of this study is to determine the prevalence and characteristics of occupational contact dermatitis in cleaning service workers at the Sudirman Campus of Udayana University.Methods: This research is a descriptive study using a cross-sectional method and uses 47 samples. Results: The prevalence of occupational contact dermatitis in cleaning services in Sudirman Campus of Udayana University is 10.6%, with the characteristics of age mostly found in 21 – 30 years (9.5%) and 31 – 40 years (18.2%), dominated by men (16.7%), working period <4 years (12.5%), duration of contact ≥3 hours (14.3%), without a history of allergies (10%), with a history of disease other skin (23.5%), good personal hygiene (7.5%), and using Personal Protective Equipment (7.3%). The dominant chemical that is used is acid (11.1%) though workers can contact more than one type of substance. The most common symptoms complained of include itching, burning or burning, redness of the skin, and peeling skin. Conclusion: The prevalence of occupational contact dermatitis in cleaning service workers at Sudirman Campus of Udayana University is 10.6% and the factors contributing are the duration of contact, gender, age, contact with chemicals, years of service, history of allergies, history of other skin diseases, personal hygiene, and the use of personal protective equipment.